Differential recognition of oligomannose isomers by glycan-binding proteins involved in innate and adaptive immunity - Gao, Chao (Sci Adv, 2021)
The recognition of oligomannose-type glycans in innate and adaptive immunity is elusive due to multiple closely related isomeric glycan structures. To explore the functions of oligomannoses, we developed a multifaceted approach combining mass spectrometry assignments of oligomannose substructures and the development of a comprehensive oligomannose microarray. This defined microarray encompasses both linear and branched glycans, varying in linkages, branching patterns, and phosphorylation status. With this resource, we identified unique recognition of oligomannose motifs by innate immune receptors, including DC-SIGN, L-SIGN, Dectin-2, and Langerin, broadly neutralizing antibodies against HIV gp120, N-acetylglucosamine-1-phosphotransferase, and the bacterial adhesin FimH. The results demonstrate that each protein exhibits a unique specificity to oligomannose motifs and suggest the potential to rationally design inhibitors to selectively block these protein-glycan interactions.